(untitled) (Romanian Biotechnological Letters, 2024)
Genetic Use Restriction Technology (GURT), also known as “terminator technology”, is a type of genetic engineering that renders seeds sterile (V-GURT) or alters a specific trait of a plant (T-GURT), preventing farmers from saving and replanting harvested seeds. GURT can also be of immense benefit to agriculture. It can be used to modify crops for improved traits, such as resistance to pests, herbicides or environmental stresses, which can ultimately improve yields, reduce the need for pesticides and herbicides, and help crops adapt to changing climatic conditions. Despite its potential benefits, GURT technology is restricted in many countries due to ethical and environmental concerns. The debate on the legalisation of GURTs is based on the main issues of food security, biological and environmental impacts, and possible monopolisation of the seed industry by a few large companies. Therefore, in this review we discuss the novelty of GURT technology in crop improvement and the contentious issues that continue to be debated by scientists, policy makers and the public.